Bond risk premia, macroeconomic factors and financial crisis in the euro area - Juan Angel García; Sebastian E. V. Werner (European Central Bank (ECB), 2016)
This paper investigates the power of macroeconomic factors to explain euro area bond risk premia using (i) a large dataset that captures the nowadays data-rich environment (ii) the Elastic Net variable selection. We find that macroeconomic factors, in particular economic activity and sentiment indicators, explain 40% of the variability of risk premia before the crisis, and up to 55% during the financial crisis, and both for core countries (from 40% to 60%) and periphery countries (from 35% to 44%). Moreover, macroeconomic factor models clearly outperform financial indicators like the CP-factor and credit default swap (CDS) premia, even in periods of significant market turbulence.
Keywords: E43; E44; G01; G12; C52; C55; 330; bond risk premium; financial crisis; macro factors; model selection; variable selection